Pengembangan Hotel Syariah dalam Tinjauan Ekonomi Islam dan Maqashid Syariah - Sri Mulyani; Kasuwi Saiban; Misbahul Munir (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
Indonesia is projected to become a center for the development of the halal industry. One of the halal industry sectors that has great potential to be developed is the halal tourism sector with its supporting sector in the form of sharia hotels. This study aims to identify and analyze the concept of sharia hotel development in Indonesia which is reviewed with an Islamic economic approach and sharia maqashid. Qualitative research method with descriptive approach is used in this research by using content analysis. The results of this study indicate that the development of sharia hotels in Indonesia is in accordance with maqashid sharia, namely not only paying attention to material aspects but also immaterial aspects. Sharia hotels have standards that must be met in the maqashid sharia framework, namely by paying attention to product aspects, service aspects, and management aspects.